PLCε regulates prostate cancer mitochondrial oxidative metabolism and migration via upregulation of Twist1 - Fan, Jiaxin (J Exp Clin Cancer Res, 2019)
BACKGROUND: Metabolic rewiring is a common feature of many cancer types, including prostate cancer (PCa). Alterations in master genes lead to mitochondrial metabolic rewiring and provide an appealing target to inhibit cancer progression and improve survival. Phospholipase C (PLC)ε is a regulator of tumor generation and progression. However, its role in mitochondrial metabolism remains unclear. METHODS: The GEO, The Cancer Genome Atlas, and the GTEx databases were used to determine Twist1 mRNA levels in tumors and their non-tumor counterparts. Fifty-five PCa and 48 benign prostatic hypertrophy tissue samples were tested for the presence of PLCε and Twist1 immunohistochemically. An association between PLCε and Twist1 was determined by Pearson’s correlation analysis. PLCε was knocked down with a lentiviral short hairpin RNA. Mitochondrial activity was assessed by measuring the oxygen consumption rate. Western blotting analyses were used to measure levels of PPARβ, Twist1, phosphorylated (p)-Twist1, p-MEK, p-ERK, p-P38, and p-c-Jun N-terminal kinase (JNK). Cells were treated with inhibitors of MEK, JNK, and P38 MAPK, and an agonist and inhibitor of peroxisome proliferator activated receptor (PPAR) β, to evaluate which signaling pathways were involved in PLCε-mediated Twist1 expression. The stability of Twist1 was determined after blocking protein synthesis with cycloheximide. Reporter assays utilized E-cadherin or N-cadherin luciferase reporters under depletion of PLCε or Twist1. Transwell assays assessed cell migration. Finally, a nude mouse tumor xenograft assay was conducted to verify the role of PLCε in tumor formation. RESULTS: Our findings revealed that the expression of PLCε was positively associated with Twist1 in clinical PCa samples. PLCε knockdown promoted mitochondrial oxidative metabolism in PCa cells. Mechanistically, PLCε increased phosphorylation of Twist1 and stabilized the Twist1 protein through MAPK signaling. The transcriptional activity of Twist1, and the Twist1-mediated epithelial-to-mesenchymal transition, cell migration, and transcription regulation, were suppressed by PLCε knockdown and by blocking PPARβ nuclear translocation. The tumor xenograft assay demonstrated that PLCε depletion diminished PCa cell tumorigenesis. CONCLUSIONS: These findings reveal an undiscovered physiological role for PLCε in the suppression of mitochondrial oxidative metabolism that has significant implications for understanding PCa occurrence and migration. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13046-019-1323-8) contains supplementary material, which is available to authorized users.